2008
DOI: 10.1186/1751-0147-50-48
|View full text |Cite
|
Sign up to set email alerts
|

Stress and its influence on reproduction in pigs: a review

Abstract: The manifestations of stress, defined as a biological response to an event that the individual perceives as a threat to its homeostasis, are commonly linked to enhanced activity of the hypothalamo-pituitary-adrenal (HPA) axis and the activation of the sympathetic adreno-medullary (SA) system. Activation of the HPA system results in the secretion of peptides from the hypothalamus, principally corticotropin releasing hormone (CRH), which stimulates the release of adrenocorticotropic hormone (ACTH) and beta-endor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
17

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(108 citation statements)
references
References 61 publications
2
89
0
17
Order By: Relevance
“…McNitt and First [33] found that placing boars for 72 h in a climatic chamber at 33°C and a relative humidity of 50% resulted in a decrease in the total spermatozoa count in the ejaculate and an increase in the percentage of spermatozoa with morphological abnormalities within about two weeks of the treatment. Similar conclusions were reached by Larsson and Einarsson [34] , who placed boars for 100 h at 35°C and a relative humidity of 40%. The results were reduced ejaculate volume and a higher percentage of abnormal spermatozoa; total sperm counts in the ejaculates, however, remained unchanged.…”
Section: The Data Presented Insupporting
confidence: 84%
See 1 more Smart Citation
“…McNitt and First [33] found that placing boars for 72 h in a climatic chamber at 33°C and a relative humidity of 50% resulted in a decrease in the total spermatozoa count in the ejaculate and an increase in the percentage of spermatozoa with morphological abnormalities within about two weeks of the treatment. Similar conclusions were reached by Larsson and Einarsson [34] , who placed boars for 100 h at 35°C and a relative humidity of 40%. The results were reduced ejaculate volume and a higher percentage of abnormal spermatozoa; total sperm counts in the ejaculates, however, remained unchanged.…”
Section: The Data Presented Insupporting
confidence: 84%
“…KOWALEWSKI, KONDRACKI, GÓRSKI BAJENA, WYSOKIŃSKA Effect of Piggery Microclimate ... Motility and morphology of sperm are sensitive indicators of heat stress [19] . The extent of morphological changes in spermatozoa depends on the duration of heat impact and on the adaptability of males to the conditions of heat stress [20] . Adaptation is less easy with higher diurnal temperature variations [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Pigs are known to be inefficient at using sweat to cool their body during high ambient temperatures. Although cutaneous water loss over the general body surface appears to be similar to man and domestic species, the pig's ability to sweat is considerably limited (Ingram 1964(Ingram , 1965Einarsson et al 2008). Stone (1981) reported that the thermal characteristics of the testis and epididymis of conscious boars ranged from 35.0 C to 36.6 C and 35.0 C to 37.0 C, respectively.…”
Section: Effect Of Heat Stress On Boar Fertilitymentioning
confidence: 99%
“…These stresses negatively affect resistance to diseases such as diarrhea [24] and pneumonia [17], as well as the meat quality [26] and reproduction [6] in a variety of animals. Recently, guidelines for the handling, housing, and feeding of pigs and laying chickens with regard to animal welfare have been introduced in Japan (http://jlta.lin.gr.jp/ chikusan/aw/aw.html).…”
mentioning
confidence: 99%